2015
DOI: 10.4046/trd.2015.78.4.380
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Bronchial Artery to Non-Sequestrated Left Upper Lobe in Massive Hemoptysis

Abstract: Systemic arterial supply from the descending thoracic aorta to the basal segment of the left lower lobe without a pulmonary arterial supply is a rare congenital anomaly within the spectrum of sequestration lung disease. The most common pattern of anomalous systemic artery to the lung arises from the descending thoracic aorta and feeds the basal segments of the left lower lobe. We report an extremely rare case of a 29-year-old woman who underwent a successful left upper lobectomy for the treatment of recurrent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“… 15 Hwang reported that the evaluation for aberrant bronchial arteries by MDCT can be useful for planning therapeutic strategies such as BAE and surgery. 16 Furthermore, 3D images were superior to two-dimensional axial images in identifying ectopic origins of bronchial arteries, even with an enlarged and tortuous bronchial artery. 14 17 Furthermore, 4D CT can be used to evaluate the haemodynamic characteristics of the vasculature or the motion of organs, in addition to morphology.…”
Section: Discussionmentioning
confidence: 98%
“… 15 Hwang reported that the evaluation for aberrant bronchial arteries by MDCT can be useful for planning therapeutic strategies such as BAE and surgery. 16 Furthermore, 3D images were superior to two-dimensional axial images in identifying ectopic origins of bronchial arteries, even with an enlarged and tortuous bronchial artery. 14 17 Furthermore, 4D CT can be used to evaluate the haemodynamic characteristics of the vasculature or the motion of organs, in addition to morphology.…”
Section: Discussionmentioning
confidence: 98%
“…Although it is necessary to decide the best approach to preserve lung function, there are no available criteria for treatment decision making. Rigorous preoperative evaluation of the perfusion area of the anomalous artery is crucial to delineate the appropriate anatomic components of the lung that should be removed 5 . This is the first report in which unnecessary lobectomy is avoided of a lung with dual arterial supply following diagnosis based on balloon occlusion anomalous arterial wedge pulmonary angiography findings.…”
Section: Figurementioning
confidence: 95%
“…Systemic arterial supply to the lung is a rare group of pathologies which include bronchopulmonary sequestration, hypogenetic lung syndrome and anomalous arterial supply without pulmonary sequestration. [ 1 ] The anomalous arterial supply without sequestration is one of the rarest forms of congenital anomaly. [ 1 2 ] It is generally incidentally detected since most of the patients are asymptomatic.…”
mentioning
confidence: 99%
“…[ 1 ] The anomalous arterial supply without sequestration is one of the rarest forms of congenital anomaly. [ 1 2 ] It is generally incidentally detected since most of the patients are asymptomatic. Here we present a case of a young male who was diagnosed to have anomalous arterial supply to the right lung without any sequestration.…”
mentioning
confidence: 99%
See 1 more Smart Citation